Peningkatan Hasil Belajar Pendidikan Agama Katolik Melalui Problem Based Learning pada Materi Aku Citra Allah yang Unik Kelas VII SMP Negeri 7 Belimbing - Sri Eva Moderani; Brigida Intan Printina (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to improve the learning outcomes of grade VII students of SMP Negeri 7 Belimbing for the 2024/2025 school year in the subject of Catholic Religious Education through the application of the Problem Based Learning (PBL) learning model. This type of research is Classroom Action Research (PTK) which is carried out in two cycles with 2 meetings each cycle. Each cycle consists of several stages, namely planning, implementation of actions, observation and reflection. The subject matter discussed was